Case Report: Two-center case series of motor-sparing nerve blocks comprised of preservative-free midazolam–buprenorphine–clonidine–dexamethasone - Williams, Brian A.; Ritter, Marsha E.; Kennedy, Patrick J.; Kmatz, Alissa M.; Abdullah, Leath; Scanlan, Rick L.; McNiffe, Nicholas J.; Fowler, William M.; Patzkowski, Michael S. (Frontiers in Anesthesiology, 2025)
The four individual cases presented include three clinical scenarios in which the operating surgeon, on behalf of the surgical patient, desired focal “conduction analgesia” without motor block to facilitate postoperative physical examination and/or the immediate advancement of physical therapy/ambulation objectives during early convalescence. The authors at two centers opted for available pharmacologic motor-sparing nerve blocks (entailing motor–sensory nerve fiber analgesia without using typical local anesthetics) as opposed to commonplace anatomic motor-sparing nerve blocks (involving local anesthetics that block sodium channels but do not target motor nerve fibers). Three of the four cases involved an acute postoperative timeline, while the fourth entailed an outpatient physical examination 6 months postoperatively in a patient with chronic, persistent surgical pain that was subsequently diagnosed with complex regional pain syndrome (CRPS). The intervention consisted of a four-medication motor-sparing nerve block (midazolam–buprenorphine–clonidine–dexamethasone), which had been previously reported. All four patients were satisfied with the short-term analgesic outcomes, and the surgeons' physical therapy and related objectives were met through the avoidance of motor block. In the latter case, which was later diagnosed as CRPS, the surgeon determined through physical examination that bony and soft-tissue healing was appropriate, obviating the need for repeat surgical exploration, thus allowing for an earlier referral to a chronic pain consultant for (ultimately) CRPS management. The described four-medication, preservative-free perineural combination, previously shown to be non-toxic in vitro and in vivo, may have important clinical applications when motor-sparing analgesia is desired in varying contexts and in cases of extreme postsurgical pain. The presentation of these four cases is followed by an aggregate data summary (n = 305 cases) of analgesic duration (mean 30.5 h, 95% CI 28.5–32.5 h) and pre-/postintervention peak pain scores (pre: mean 7.8/10 [95% CI 7.5–8.0]; post: mean 6.3/10 [95% CI 6.0–6.6]) after the described four-drug nerve block intervention, derived from quality improvement data at one of the two contributing author centers.